2021
DOI: 10.1371/journal.pone.0249753
|View full text |Cite
|
Sign up to set email alerts
|

Condom application skills and self-efficacy in youth: A systematic review and meta-analysis

Abstract: Globally, and in the United States (U.S.) specifically, rates of reported sexually transmitted infections (STIs) have been steadily increasing and are especially high among youth aged 13–25 years. Using condoms correctly and consistently is an effective STI prevention measure for sexually active youth, yet public health endeavors tend to focus only on condom use consistency. Directly measuring condom application is challenging and expensive. Alternative tools evaluate this behaviour, but little evidence exists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
4
0
1
Order By: Relevance
“…The demarcation points in 2004 suggested that the burden of unsafe sex was under management and control in 2004. The underlying reason could be attributed to the popularity of condoms, the developments in medical technology, and increased awareness of reproductive health 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The demarcation points in 2004 suggested that the burden of unsafe sex was under management and control in 2004. The underlying reason could be attributed to the popularity of condoms, the developments in medical technology, and increased awareness of reproductive health 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…We cannot possibly rule out the overestimation of condom use reported by participants themselves. However, the extent of condom protection was always difficult to quantify because of many methodological challenges inherent in studying privacy behavior that cannot be directly observed or measured ( 32 , 33 ). Finally, this study was based on the secondary database which did not collect HCV status of index cases and other risk factors like STIs or genital ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in theoretical perspectives and labeling of motivation concepts make it difficult to organize, accumulate, and integrate research on motivation for health-related behavior, despite the fact that so much work has been done. Indeed, in contrast to other health psychology constructs, such as self-efficacy and outcome expectancies, for which researchers working within specific healthbehavior content areas have characterized and integrated findings across theoretical traditions (Ferrand et al, 2021;Newby et al, 2021;Bohlen et al, 2022;Pinquart and Borgolte, 2022), it is more difficult to characterize research on "motivation" in the broader field of health psychology or within specific content areas. 1 Thus, despite the fact that motivation is clearly important to predicting, understanding, and changing health-related behaviors, the heterogeneity in motivation labels and theoretical approaches is a major barrier to synthesizing research on motivation within health-related behavior domains.…”
Section: Introductionmentioning
confidence: 99%